Redução de danos: estratégia de cuidado com populações vulneráveis na cidade de Santo André - SP Harm reduction: strategic care for vulnerable populations in the city of Santo André - SP - Silvia Moreira da Silva; Ana Lucia Spiassi; Decio de Castro Alves; Daniela de Jesus Guedes; Reinaldo de Oliveira Leigo (Universidade de São Paulo, 2009)
A Unidade de Redução de Danos (URD) da Secretaria Municipal de Saúde de Santo André, compreendida como instrumento do serviço de saúde em atuação avançada, tem por finalidade transformar a situação de saúde de sujeitos que fazem parte de grupos sociais estigmatizados e, portanto, vulnerabilizados; são indivíduos que circulam ou trabalham nas ruas - usuários de drogas, michês, mulheres profissionais do sexo, homens que fazem sexo com homens, adolescentes em situação de exploração sexual, transexuais, travestis, lésbicas e mulheres que trabalham em casas de programas. Nosso objetivo é assegurar aos indivíduos desses grupos o direito à saúde e, baseados no princípio de Integralidade do SUS, apoiar o acesso a outros direitos sociais. Desde 2002, através do trabalho de campo, foi possibilitada a vinculação de 240 profissionais do sexo, 120 travestis, 10 crianças e adolescentes, 28 usuários de droga injetável e usuários de crack, que até então não tinham acesso aos recursos e dispositivos de saúde do Município. The Harm Reduction Unit (HRU) of the Municipal Health Department of Santo André (state of São Paulo) is a working tool for healthcare that has the purpose of transforming the health situation of individuals who are part of socially stigmatized, therefore vulnerable, groups. These are individuals who spend their lives or work on the streets: drug users, male prostitutes, female sex workers, men who have sex with men, sexually exploited adolescents, transsexuals, transvestites, lesbians and women working in brothels. The HRU's potential benefits were indicated to be: it improved healthcare and condom use; decreased drug use; improved seeking and access to healthcare services; decreased material sharing for drug use; improved decision-making capacity. HRU's actions have gone beyond prevention of health damage, as it has promoted broader transformations such as awareness of social rights in general and health rights in particular, along with actions towards making these rights apply, based on the principle of integrality of SUS (Brazil's National Health System). Since 2002 we have assisted, through outreach work, 240 prostitutes, 120 travestites, 10 sexually exploited adolescents and 28 drug users (intravenous and crack).